2012
DOI: 10.1093/humupd/dms024
|View full text |Cite
|
Sign up to set email alerts
|

Female reproduction and type 1 diabetes: from mechanisms to clinical findings

Abstract: Despite improvements in insulin therapy, T1D patients still suffer many reproductive problems that warrant specific diagnoses and therapeutic management. Similar to other states of metabolic stress, T1D represents a challenge to the correct functioning of the reproductive axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 180 publications
2
120
1
10
Order By: Relevance
“…These data suggest that female sex as a protective factor against the development of microvascular complications may be abolished if diabetes onset is before or during puberty, thus implicating hormonal changes associated with puberty in the development of microvascular complications. Puberty is characterised by changes in the hypothalamus-pituitary-gonadal (HPG) axis, including pituitary growth hormone, insulin-like growth factor I, gonadotrophins, luteinising hormone and follicle-stimulating hormone [35]. Type 1 diabetes has been shown to cause disturbances in the HPG axis; in girls with type 1 diabetes, these disturbances are associated with Age at menarche (years)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that female sex as a protective factor against the development of microvascular complications may be abolished if diabetes onset is before or during puberty, thus implicating hormonal changes associated with puberty in the development of microvascular complications. Puberty is characterised by changes in the hypothalamus-pituitary-gonadal (HPG) axis, including pituitary growth hormone, insulin-like growth factor I, gonadotrophins, luteinising hormone and follicle-stimulating hormone [35]. Type 1 diabetes has been shown to cause disturbances in the HPG axis; in girls with type 1 diabetes, these disturbances are associated with Age at menarche (years)…”
Section: Discussionmentioning
confidence: 99%
“…Shaded areas represent 95% CIs. The area above the dotted line at zero represents increased risk and the area under the dotted line represents a decreased risk delayed ovarian maturation and sex hormone production, leading to delayed menarche [35]. Thus, there appears to be a strong link between sex hormones, delayed menarche and the development of diabetic microvascular complications associated with type 1 diabetes [36].…”
Section: Discussionmentioning
confidence: 99%
“…The women also present insufficient Luteinizing hormone (LH) and follicle stimulating hormone (FSH), which have mostly been associated with a lack of residual insulin secretion (33). The poor metabolic control observed in a majority of these patients explain the perturbations (34). The hypogonadotropic hypogonadism seen in amenorrheic diabetic females has been shown to be similar to that linked to other metabolic stress forms, including strenuous exercise and anorexia nervosa (35).…”
Section: Pituitary-hypothalamic Functionmentioning
confidence: 96%
“…The hypogonadotropic hypogonadism seen in amenorrheic diabetic females has been shown to be similar to that linked to other metabolic stress forms, including strenuous exercise and anorexia nervosa (35). However, other reports have shown that diabetic patients with secondary amenorrhea due to hypogonadotropic hypogonadism failed to recover following theimprovement in metabolic control (36), implying that a certain group of diabetic patients is prone to hypogonadism (34).The hypothalamic origin of the decreased levels of gonadotropin in amenorrheic and diabetic patients has been explained (25,26). Abnormalities of gonadotropin-releasing hormone (GnRH) pulse generator are hypothesized on LH pulses studies, indicating the secretory activity of the GnRH neurons (37).…”
Section: Pituitary-hypothalamic Functionmentioning
confidence: 98%
See 1 more Smart Citation